Assessment of Instructions on Protection Against Food Contaminated with Radiocesium in Japan in 2011. Issue 6 (7th September 2017) - Seto, Mayumi; Uriu, Koichiro; Kawaguchi, Isao; Yokomizo, Hiroyuki
Abstract: The Japan Ministry of Health, Labour and Welfare (MHLW) has published instructions for radiological protection against food after the Fukushima Daiichi nuclear power plant accident in 2011. Following the instructions, the export and consumption of food items identified as being contaminated were restricted for a certain period. We assessed the validity of the imposed restriction periods for two representative vegetables (spinach and cabbage) grown in Fukushima Prefecture from two perspectives: effectiveness for reducing dietary dose and economic efficiency. To assess effectiveness, we estimated the restriction period required to maintain consumers' dose below the guidance dose levels. To assess economic efficiency, we estimated the restriction period that maximizes the net benefit to taxpayers. All estimated restriction periods were shorter than the actual restriction periods imposed on spinach and cabbage from Fukushima in 2011, which indicates that the food restriction effectively maintained consumers' dietary dose below the guidance dose level, but in an economically inefficient manner. We also evaluated the response of the restriction period to the sample size for each weekly food safety test and the instructions for when to remove the restriction. Stringent MHLW instructions seemed to sufficiently reduce consumers' health risk even when the sample size for the weekly food safety test was small, but tended to increase the economic cost to taxpayers.